THE SPECIFICS OF DISTANCE METHODOLOGICAL SUPPORT FOR FOREIGN LANGUAGE TEACHERS IN A FOREIGN LANGUAGE ENVIRONMENT - Guzhelya, Dmitry; Kurilenko, Victoria; Biryukova, Yulia (Revista Inclusiones, 2019)
The article reveals the essence and linguodidactic potential of distance methodological support for language teachers. Reviews of available scientific literature and existing courses show that, being in a foreign language environment, teachers need additional methodological support. In order to achieve this particular goal it is proposed to create a mechanism for developing innovative means of distance methodological support based on the Universarium open digital educational system, which has great potential in the field of information technology. This digital platform is the basis for developing a training portal, consisting of the following sections: (1) Forming the learning path (adaptational component); (2) Improving professional skills (educational component); (3) Providing consultancy and methodological support (consultative and adjusting component); (4) Teacher’s personal account (resulting component); (5) Discussing professional issues (interactive component); and (6) Distance methodological support service module (coordination and technological component). The portal efficiency was confirmed by an experiment.